The Influence of Computer-Based Learning Media Tutorials on Students' Spatial Abilities In Mathematics - Kamid Kamid; Sofnidar Sofnidar; Wardi Syafmen; Mujahidawati Mujahidawati; Roseli Theis; Khairul Anwar (JTP - Jurnal Teknologi Pendidikan, 2020)
Abstract: In 21st century learning students is required to be more active in learning than teachers, therefore this study aims to determine whether there is an influence between computer-based learning media tutorials and students' spatial abilities in mathematics. Using quantitative descriptive. Where, the number of samples in this study were 240 students from SMP 11 Jambi City who used purposive sampling technique. Data were then analyzed with the help of the SPSS 21 application to find descriptive statistics in the form of mean, min, max, and category as well as inferential statistics using simple regression. The results obtained in this study are dominant in both the spatial abilities of students in mathematics. With this reinforced by the existence of a relationship and influence between computer-based learning media tutorials with students' spatial abilities in mathematics as seen from the sig value below 0.025, which is 0.016 and has a contribution of 72.6%.